Hibiscus sabdariffa L. previne alterações na composição corporal e na função e reatividade das vias aéreas de ratos submetidos a um modelo de asma exacerbada pela obesidade: determinação do mecanismo de ação - Ferreira, Sarah Rebeca Dantas (2022)
Obesity and asthma combined result in an asthma phenotype with more severe symptoms and reduced response to corticosteroid treatment; however, the exact mechanism responsible for these changes remains unclear. In this context, a promising drug is Hibiscus sabdariffa L., popularly known as “hibiscus”, which has already shown anti-obesity activity and spasmolytic action in guinea pig trachea. Thus, the aim of this work was to standardize and implement a animal model of obesity-exacerbated asthma employing a high glycemic index diet (HGLI) and ovalbumin (OVA), characterizing in vivo and in vitro, morphologically, and functionally, the alterations induced by the combined diseases, evaluating also whether treatment with hibiscus would prevent the changes induced by them, characterizing its mechanism of action. Wistar rats (n = 5-6) were divided into control (CG), obese (OG), asthmatic (AG), obese asthmatic (OAG), obese asthmatic dexamethasone (OADEXAG), obese asthmatic hibiscus 250 mg/kg (OAH250G), obese asthmatic hibiscus 500 mg/kg (OAH500G) and obese asthmatic hibiscus 1000 mg/kg (OAH1000G). The experimental protocols were approved by CEUA/UFPB (5975030920). It was observed that obesity-related parameters, such as body weight, waist circumference, body mass index (BMI), and adiposity index were increased in OG and OAG. Treatment with dexamethasone caused weight loss compared to OAG, however, it did not reverse the increase in the other observed parameters. Hibiscus at doses of 500 and 1000 mg/kg prevented the increase in weight, BMI, abdominal circumference and adiposity. Histologically, an increase in the diameter of the adipose tissue in the animals fed with HGLI (OG and OAG) has been observed with prevention of these in OADEXAG and OAH500G. To characterize the implantation of asthma, lung function was measured using the spirometry technique (days 1, 12 and 21 of asthma induction) and no change in respiratory rate was observed, although a reduction in tidal volume and volume-minute on the 21st in AG and OAG has been reached, and this change was not reversed in OADEXAG and OAH500G. Lung histology demonstrated exacerbation of peribronchovascular inflammation in OAG compared to isolated diseases, as well as smooth muscle hypertrophy and extracellular matrix remodeling compared to CG. Functionally, the trachea was used to assess contractile and relaxing reactivity and elucidate the mechanism of action. Animals that were previously sensitized with OVA showed a contractile response to the allergen (AG and OAG), which was even greater in OAG and without reversion in OADEXAG or OAH500G. The electromechanical or histamine-induced contraction do not seemed to be involved in the diseases, with the exception of AG, which showed an increase in contractile efficacy with no change in potency against histamine. Otherwise, in the cumulative concentration-response curve to carbachol (CCh) has been observed an increase in contractile efficacy in OG, AG and OAG, with OAG being even greater than AG and with no change in potency between groups. This increase was not altered in OAH250G, however OAH500G and OAH100G prevented it, without changing the potency. On the other hand, the relaxing reactivity to nifedipine and aminophylline were not altered between the groups. While isoprenaline-induced relaxation showed reduced efficacy in OG, AG and OAG, when compared to CG. In the elucidation of the mechanism of contractile hyperreactivity to CCh, the probable participation of the superoxide anion and the cyclooxygenase products in asthma was characterized, the first being also a target of the OAH500G mechanism. In contrast, the participation of hydrogen peroxide, the nitric oxide pathway and 5-lipoxygenase products do not seem to be involved in the mechanisms of disease or hibiscus. However, a positive modulation of the Rho kinase pathway in GOA was evidenced, which was prevented by treatment of hibiscus. In view of these results, it is concluded that the obesity-exacerbated asthma model was implanted, which is resistant to treatment with dexamethasone, probably due to increased RhoA/ROCK activity. This effect is prevented by the treatment with hibiscus, becoming a promising drug for the treatment of this combined conditions.